You've got this : a student's guide to well-being at university and beyond - Alexander, Rachael (Critical Publishing, 2022)
Student life can be overwhelming, and it is not surprising that you might struggle to cope sometimes. This book guides you through your student journey with simple and effective strategies to help you take ownership of your mental health and stay in control.